PENGGUNAAN SOFTWARE GEOGEBRA PADA MATAKULIAH MATEMATIKA I MATERI INTEGRAL - Amiruddin Amiruddin; Esterina Natalia Paindan (STKIP Andi Matappa, 2020)
The research which aimed to discover the enhancement mathemtical understanding of STT Migas Balikpapan students in the integral material mathematics I course. The research was experiment research. The population was all of the students of STT Migas Balikpapan who take mathematics I in the first semester, the samples were selected one class by conducting purposive sampling techniques. The research instrument is a test description to measure the level of mathematical understanding of integral material. The design in this research was a quasi experimental design with one group pretest-posttest, the data obtained were anlyzed using the N-Gain Score. Based on the results of the research, the pretest average value was 38.33, after using geogebra the posttest average score was 74,17, with an N-Gain value of 0.62 in the medium category and for the interpretation of the effectiveness of N-Gain it was 62% in other word geogebra is categorized as quite effective, so that this research can be concluded that the use of geogebra can improve students mathematical understanding of integral